(untitled) (Archive of Conferences, 2022)
The mechanism of adhesion of basalt-plastic rods with concrete is considered, as well as the advantages and disadvantages of composite reinforcement, the area of application of composite reinforcement , we also give the comparative characteristics of composite and metal fittings, we give the definition of composite and basalt-plastic fittings, consider the analysis of the resistance of highstrength steel and fiberglass reinforcement in aggressive environments